(untitled) (Bangladesh Journal of Plant Taxonomy, 2020)
This study provides basic taxonomic data on Liliopsida (monocotyledons) and Pteridophyta of the representative homestead areas of Dhaka, Gazipur, Manikganj and Tangail districts of Bangladesh. The monocotyledons and pteridophytes, growing naturally in the homstead areas, are composed of total 137 and 16 species under 84 and 13 genera belonging to 22 and seven families, respectively. A total of 20, 13, 19 and 17 species respectively, occur exclusively in the homesteads of Dhaka, Gazipur, Manikganj and Tangail districts and only 22 species are common there. Poaceae with 53 species is the largest family and Cyperus with 12 species is the largest genus in monocotyledons. Pteridaceae with eight species and Pteris with three species are the better represented family and genus, respectively in pteridophytes. Total 136 species are appeared as herbs that are followed by 11 species of trees and six species of shrubs. A total of 119 species are documented as economically useful. This study identifies a number of active threats to the flora of the study area, and suggests to launch adequate management and awareness building programs for the homestead people in order to ensure effective conservstion and sustainable use and development of plant genetic resources in the homestead areas of this region. Bangladesh J. Plant Taxon. 27(2): 407-425, 2020 (December)